2013
DOI: 10.1101/gad.221374.113
|View full text |Cite
|
Sign up to set email alerts
|

Real-time recording of circadian liver gene expression in freely moving mice reveals the phase-setting behavior of hepatocyte clocks

Abstract: The mammalian circadian timing system consists of a master pacemaker in the suprachiasmatic nucleus (SCN) in the hypothalamus, which is thought to set the phase of slave oscillators in virtually all body cells. However, due to the lack of appropriate in vivo recording technologies, it has been difficult to study how the SCN synchronizes oscillators in peripheral tissues. Here we describe the real-time recording of bioluminescence emitted by hepatocytes expressing circadian luciferase reporter genes in freely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
196
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(214 citation statements)
references
References 50 publications
16
196
1
1
Order By: Relevance
“…S1 F-I). Of note, using luciferase reporter mice, Saini et al (8) observed a similar pattern of expression for Per2, RevErbα, and Bmal1 in RF livers. That early RF metabolic changes were similar to those generated under starvation and that RF and starvation altered the same CC components prompted us to investigate how metabolic alterations may impair PCC during RF.…”
Section: Resultsmentioning
confidence: 72%
“…S1 F-I). Of note, using luciferase reporter mice, Saini et al (8) observed a similar pattern of expression for Per2, RevErbα, and Bmal1 in RF livers. That early RF metabolic changes were similar to those generated under starvation and that RF and starvation altered the same CC components prompted us to investigate how metabolic alterations may impair PCC during RF.…”
Section: Resultsmentioning
confidence: 72%
“…Adenovirus mediated gene transfer is widely used to modulate the expression of genes in the liver and known to primarily transduce hepatocytes (51)(52)(53)(54)(55). However, the method has limitations that adenovirus will be cleared by host immune cells and will not sustain the transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that also the peripheral clocks show daily rhythms, but the coherency of these rhythms seems to depend strongly on the SCN as some studies showed that peripheral tissues lost their daily rhythmicity after an SCN lesion (Akhtar et al 2002;Sakamoto et al 1998;Yoo et al 2004;Yamazaki et al 2000). However, more recent studies Saini et al 2013;Tahara et al 2012) showed that the peripheral clock genes may maintain their daily rhythmicity, although with a different amplitude, after an SCN lesion. These recent findings indicate that the rhythms of peripheral clocks apparently can also be synchronized with the environmental day/night changes through extra-SCN pathways.…”
Section: Introductionmentioning
confidence: 93%